When Being Men Matters: Exploring Health Literacy Determinants in a rural community, Malaysia - Roslan, Dalila; Azzani, Meram; Abdullah, Nik Nairan; Azhar, Zahir Izuan; Mat Ruzlin, Aimi Nadira; Chen, Xin Wee; Jamil, Ahmad Taufik; Selamat, Mohamad Ikhsan (European Journal of Sustainable Development, 2025)
Promotion programs are widely conducted in rural communities to improve health outcomes. Hence, understanding the health literacy (HL) of a community is crucial in planning purposeful health promotion programs. However, HL data on the rural setting in Malaysia is scarcely known. This study aimed to determine the prevalence and determinants of HL among adults living in the district of Sabak Bernam, Malaysia. 382 villagers participated in this cross-sectional study by answering questionnaires. Most of the villagers had adequate HL, with 14.1% having limited HL. This study established that the elderly, males, and those with non-communicable disease (NCD) comorbidities were significantly associated with limited HL. Whereas having formal education and being non-Malay residents were protective determinants. Being male was a predictor of having limited HL in this research. These findings highlight the importance of tailored health promotion programs focusing on vulnerable groups, including elderly men with NCD. Public health activities in rural communities should consider demographic, cultural and educational status when developing health education materials and interventions. Improved health interventions, curated to address these identified determinants, are the stepping stone towards bridging health literacy disparities in alignment with other efforts to achieve Sustainable Development Goals (SDGs) 3-5 and 10. Keywords: Health literacy, rural, elderly, men, health promotion, community, non-communicable diseases.